2022
DOI: 10.1002/jwmg.22287
|View full text |Cite
|
Sign up to set email alerts
|

Columbian sharp‐tailed grouse brood success and chick survival in a wind‐energy landscape

Abstract: Columbian sharp-tailed grouse (Tympanuchus phasianellus columbianus) have experienced range-wide population declines, primarily as a result of habitat loss or degradation, and currently occupy <10% of their historical range. Expansion of wind-energy development across the current, occupied Columbian sharp-tailed grouse range is a potential threat to the subspecies. To assess the potential effects of wind-energy development on vital rates of Columbian sharp-tailed grouse offspring, we monitored 68 broods of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…For instance, warmer temperatures during nesting and brood rearing can benefit production of Columbian sharp‐tailed grouse, unless temperatures are extreme and result in heat stress for young chicks (Flanders‐Wanner et al 2004 a ). Precipitation prior to and during nesting benefits production, but studies reported mixed results regarding the effects of precipitation directly after hatch on chick survival or production (negative, Flanders‐Wanner et al 2004 a , Goddard and Dawson 2009, positive, Proett et al 2022). Exposure to cold and wet conditions can act as a mortality source on young chicks (Manzer and Hannon 2007), but the mixed results of past studies suggest regional conditions (e.g., vegetation composition and condition, aridity) might dictate whether post‐hatch precipitation has beneficial or detrimental effects on recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, warmer temperatures during nesting and brood rearing can benefit production of Columbian sharp‐tailed grouse, unless temperatures are extreme and result in heat stress for young chicks (Flanders‐Wanner et al 2004 a ). Precipitation prior to and during nesting benefits production, but studies reported mixed results regarding the effects of precipitation directly after hatch on chick survival or production (negative, Flanders‐Wanner et al 2004 a , Goddard and Dawson 2009, positive, Proett et al 2022). Exposure to cold and wet conditions can act as a mortality source on young chicks (Manzer and Hannon 2007), but the mixed results of past studies suggest regional conditions (e.g., vegetation composition and condition, aridity) might dictate whether post‐hatch precipitation has beneficial or detrimental effects on recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, annual fluctuations in weather can affect vital rates for Columbian sharp‐tailed grouse. Drought can limit forb growth and insect production, which serve as important food resources for chicks (IDFG 2015), and therefore chick survival and recruitment can be reduced during drought (Collins 2004, Flanders‐Wanner et al 2004 a , Proett et al 2022). Drought also affects risk of wildfire (Pilliod et al 2017), which has the potential to rapidly change the composition of shrub‐steppe and grassland ecosystems and directly affect cover and food available during the breeding season (Hoffman et al 2015).…”
Section: Variables Predicted Effects Explanation Spatial Scale (Grain...mentioning
confidence: 99%